2022
DOI: 10.5815/ijisa.2022.05.01
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Management and Federated Learning Adaptation on Healthcare Management System

Abstract: Recently, health management systems have some troubles such as insufficient sharing of medical data, security problems of shared information, tampering and leaking of private data with data modeling probes and developing technology. Local learning is performed together with federated learning and differential entropy method to prevent the leakage of medical confidential information, so blockchain-based learning is preferred to completely eliminate the possibility of leakage while in global learning. Qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The study found that the system improved transparency and traceability, reduced transaction costs, and enhanced trust among supply chain participants. In addition to these studies, researchers have also developed various metrics and frameworks to evaluate the effectiveness of blockchain-based models in enhancing trust in supply chain management [23][24][25][26]. Overall, the analysis of blockchain-based models in supply chain management suggests that they can enhance trust by improving transparency, reducing fraud and counterfeiting, and enabling secure and reliable data sharing among supply chain participants (in Fig.…”
Section: Model and Methodsmentioning
confidence: 99%
“…The study found that the system improved transparency and traceability, reduced transaction costs, and enhanced trust among supply chain participants. In addition to these studies, researchers have also developed various metrics and frameworks to evaluate the effectiveness of blockchain-based models in enhancing trust in supply chain management [23][24][25][26]. Overall, the analysis of blockchain-based models in supply chain management suggests that they can enhance trust by improving transparency, reducing fraud and counterfeiting, and enabling secure and reliable data sharing among supply chain participants (in Fig.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Trust is the key to the public's compliance with policies aimed at controlling epidemics (e.g., physical isolation, vaccination). People who trust the government are more likely to comply with the rules (Blair et al, 2022;Rauf et al, 2022;Shanka and Menebo, 2022), so it is the basis of social interaction (Uslaner, 2002;Turgay, 2022) and decision-making (Yamagishi and Kiyonari, 2000). During the COVID-19 epidemic, the lack of trust may lead to nonvaccinated people and noncompliance with preventive measures, which may overwhelm the medical system (Stefaniak et al, 2022).…”
Section: Introductionmentioning
confidence: 99%